Dynamic impact analysis of masonry buildings subjected to flood actions. (15th July 2018) - Lonetti, Paolo; Maletta, Roberta
Highlights: A numerical approach based on ALE formulation, two-phase fluid flow is developed. The effects of floods on buildings in terms of damage variables are investigated. Several damage mechanisms on masonry structures due to FSI are considered. Comparisons with results arising from existing codes are developed. DDCs are evaluated to identify the vulnerability of the structure under flood actions. Abstract: The effects of floods on buildings described in terms of damage phenomena and collapse mechanisms are investigated. A comprehensive numerical approach simulating the fluid–structure interaction is herein proposed integrating (a) an ALE formulation, (b) a two-phase fluid flow, and (c) a refined finite-element structural modelling. Several potential structural failures are considered for the structure, whose activation conditions are discussed, in terms of both fluid and structural characteristics. A sensitivity study is performed in order to study the loading induced by the flood and the corresponding structural effects (e.g. internal stress/forces). A comparison between flood actions obtained through numerical simulations and with formulations available in literature is presented, with the specific purpose of emphasize the differences due to the dynamic amplification effects. As main novel results, dimensionless abacuses providing the structural safety factor as function of geometrical structural properties and inundation characteristics are provided. Such a result is very valuable both for researchers and practitioners in the field of flood risk assessment.